Polymer coating, germination and vigor of broccoli seeds - Almeida, Celina de (2005)
Brassica oleracea var italica occupies a special place in the internal and external market of vegetables seeds. Vegetables producers demand seeds with high degree of purity, germination and vigor, since seeds' quality is the basis for the success of the production. In this work, broccoli seeds were coated in a spouted bed, by an aqueous suspension of hidroxy-ethyl-cellulose. Effects of the operating variables: spouting air temperature, atomizing air pressure and coating suspension flow rate over the dependent variables: seeds germination, seeds accelerated aging and the speed of seeds germination in soil, were investigated in a factorial scheme trial. The maximum processing time was 120 min. A totally randomized experiment evaluated and compared seeds germination and vigor of the coated and non-coated seeds. There was no identifiable, pronounced difference on germination of coated and non-coated seeds, accelerated aging of seeds, and speed of seeds germination in the soil. Coating with hidroxy-ethyl-cellulose in the spouted bed did not alter broccoli seeds physiologic quality. The surface of coated seeds presented satisfactory distribution and spreading of the polymer film, uniform and individual coating and homogeneous aspect.